BEAM scheme development work based on arduino pro micro c using solar panel - Yevsieiev, V. (Видавництво ОНТУ, 2023)
This work is devoted to the coverage of BEAM robotics development issues. The author provides a comparative analysis between the BEAM robot and a classic mobile robot according to various criteria and has developed a BEAM robot scheme based on Arduino Pro Micro using a Solar Panel.
Keywords: BEAM robotics; Scheme of a BEAM robot; Arduino Pro Micro; Solar Panel